Evaluation of a sensitive/less-sensitive testing algorithm using the 3A11-LS assay for detecting recent HIV seroconversion among individuals with HIV-1 subtype B or E infection in Thailand - B. S. Parekh (2018)
The development of a serologic algorithm to determine recent HIV seroconversion, using sensitive/less-sensitive testing strategies, has generated widespread interest in applying this approach to estimate HIV-1 incidence in various populations around the world. To evaluate this approach in non-B subtypes, longitudinal specimens (n = 522) collected from 90 incident infections among injecting drug users in Bangkok (subtype B infection, n = 18; subtype E infection, n = 72) were tested by the 3A11-LS assay. Standardized optical density (SOD) was calculated, using median values, and the window period between seroconversion as determined by sensitive and less sensitive tests was estimated by a maximum-likelihood model described previously. Our results show that the mean window period of the 3A11-LS assay was 155 days (95% CI, 128-189 days) for subtype B but was 270 days (95% CI, 187-349 days) for subtype E specimens from Thailand. About 4% of individuals with incident subtype E infections remained below the threshold (SOD of 0.75), even 2 years after seroconversion. Among the patients with clinical AIDS and declining antibodies, none of the 7 individuals with subtype B, but 10 (8.7%) of 115 with subtype E infections, were misclassified as recent infections. Lowering the cutoff to an SOD of 0.45 for subtype E specimens resulted in a mean window period of 185 days (95% CI, 154-211 days), with all individuals seroconverting, and reduced the number of subtype E-infected patients with AIDS who were misclassified as having recent infection to 2.6%. Our results demonstrate that the 3A11-LS assay has different performance characteristics in detecting recent infections among individuals infected with subtypes B or E. Determining appropriate cutoffs and mean window periods for other HIV-1 subtypes will be necessary before this approach can be reliably implemented in settings where non-B subtypes are common.